Chemical Constituents and Antitumor Mechanisms of Artemisia - Kamarya, Yasin; Lijie, Xia; Jinyao, Li (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: At present, chemotherapy is still the main treatment for cancer, but its side effects and multidrug resistance limit the therapeutic efficacy. Natural products are the important sources for the development of antitumor drugs with higher efficiency and lower toxicity. Artemisia contains a variety of antitumor constituents, which can induce tumor cell apoptosis and cell cycle arrest, inhibit tumor angiogenesis, and accelerate iron ion-mediated oxidative damage. Objective: This paper provides a focused, up-to-date, and comprehensive overview of the antitumor active constituents and mechanisms of Artemisia. Methods: The relevant references on Artemisia and its bioactive components were obtained from scientific databases, including PubMed, Web of Science, and Science Direct. Results: We have summarized the current progress about on the bioactive components and mechanisms of Artemisia. The application prospect of active components of Artemisia in cancer prevention and treatment has also been discussed. Conclusion: This review may provide new ideas for the follow-up treatment of cancer and contribute to the development of safe and effective antitumor drugs.
Keywords: Artemisia